PENGARUH PENGGUNAAN MODUL DIGITAL INTERAKTIF TERHADAP MINAT DAN HASIL BELAJAR MATERI PECAHAN KELAS IV SDN 2 KLESEM - Hengkang Bara Saputro; Olivia Rizky Febriani (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effect of interactive digital module learning media on interest and learning outcomes in class IV SDN 2 Klesem material. The research approach used in this research is quantitative research, with a one-group pretest-posttest design. The sample in this study were 27 fourth grade students at SDN 2 Klesem consisting of 11 female students and 16 male students. The instrument of interest in this study uses a questionnaire and learning outcomes use test scores. Data analysis techniques using the t test with a significance level of 5%. Based on the results of the t test analysis (Hypothesis 1 test), the t count (8.387) > t table (2.056) is obtained, and the p value (0.000) < 0.05, these results conclude that there is an effect of using interactive digital modules on interest in learning fraction material class IV SDN 2 Klesem. The results of the t test analysis (Hypothesis 2 test) obtained t count value (11.760) > t table (2.056), and p value (0.000) < 0.05, these results concluded that there was an effect of using interactive digital modules on learning outcomes for class fraction material IV SDN 2 Klesem